VBAC or elective caesarean? a midwife-led shared decision making approach to choice following a caesarean section. (18th April 2012) - Leader, CH; Macphail, S; Ayuk, P; Robson, SC
Abstract : Background: Women with one prior caesarean face a choice between an attempted vaginal birth after caesarean (VBAC) or a caesarean section (CS). There is no evidence that either choice is associated with better outcomes. NICE states that women's preferences should guide the choice. In 2010 a midwife-led shared decision making (SDM) approach was introduced into the care pathway of women with one prior CS. This aim of this study was to evaluate this approach. Implementation: 103 women were sent a decision aid (information leaflet and Ottawa Decision Guide) prior to a VBAC clinic appointment at 20 weeks where mode of delivery was discussed / agreed by a midwife trained in SDM. A questionnaire was administered after the consultation ascertaining involvement in the decision making process. Results: 91% of women reported they had engaged with the decision aid. 42% opted for VBAC, 31% for ELCS, and 27% deferred the decision to 36 weeks (when 46% chose VBAC). Of 75 women who had made a decision at 20 weeks, 6 changed their choice at 36 weeks (all from VBAC to CS). 47% returned questionnaires; 62/38% strongly agreed/agreed they had been given the pros and cons of each choice; 76/24% strongly agreed/agreed that they had been involved in decisions and 74/26% strongly agreed/agreed that they were involved as much as they wanted to be. Conclusion: Results suggest that women engaged with the decision aids and benefited from a SDM approach. The small number of women who altered their decision at 36 weeks suggests decision quality may be better when a SDM approach is adopted.